Measuring intermittent exercise performance using shuttle running - Ali, A.; Foskett, A.; Gant, N. (Journal of Sports Sciences, 2014)
The aim of this study was to include self-paced exercise within a modified Loughborough Intermittent Shuttle Test (LIST-P) in order to quantify key performance variables not possible with prescribed workloads. Sixteen male games players performed two trials of the LIST-P, at least 7 days apart. The LIST-P incorporates 4 × 15-min blocks of "prescribed-pace" activity (participants exercise in time to audible signals) followed by 2 × 15-min blocks of "self-paced" running (no audible signals). Distances covered and mean speeds were monitored during self-paced exercise. Total distance covered (12.54 ± 0.45 km vs. 12.64 ± 0.32 km; P = 0.10) and mean speed (8.37 ± 0.31 km/h vs. 8.44 ± 0.22 km/h; P = 0.10) was similar between trials. Other indices also showed the test to be reliable (Pearson`s correlation = 0.89 and 0.90 (P < 0.01), total distance and mean speed, respectively; intraclass correlation coefficient = 0.88 and 0.88 (P < 0.01); standard error of measurement = ±0.13 km and ±0.09 km/h; coefficient of variation (CV) = 1.7% and 1.7%; ratio limits of agreement = 1.00 */÷1.03 and 1.01 */÷1.04). Sprint time was also similar between trials (2.60 ± 0.19 s vs. 2.64 ± 0.23 s; P = 0.29). Incorporating self-paced exercise within an established intermittent shuttle running test appears to be a sensitive means of quantifying key performance variables for multiple-sprint sports research.